PENGEMBANGAN MINIATUR ALAT TRANSPORTASI DARAT PADA PEMBELAJARAN GEOMETRI DI KELAS IV SD - Tanti Nurwanti; Dinda Yarshal (Jurnal Inovasi Penelitian, 2023)
This development research aims to determine the process of developing miniature media for land transportation in geometry learning that is suitable for use in elementary schools. This research is a type of research and development (Research and Development) using the ADDIE development model which consists of 5 stages, namely. Analysis (Analysis). Design (Design). Development (Development), Implementation (Implementation) and Evaluation (Evaluation). In this development the ADDIE development model is carried out only up to the 3rd stage, namely Development. The instruments used were a material expert questionnaire, a media expert questionnaire and a learning expert questionnaire to determine the feasibility of miniature land transportation media in the developed geometry learning. Based on the validation results from the material expert validator, a percentage of 80% was obtained with the "Decent" criteria. From the validation results of media experts, it was obtained a percentage of 96% with the criteria of "Very Eligible". From the results of the validation of learning experts, a percentage of 92% was obtained with the "Very Eligible" criteria. From the assessment of the three expert validators, it can be said that the miniature media for land transportation in geometry learning which was developed "Very Feasible" is used in the geometry learning process in class IVSD